2016
DOI: 10.1017/jns.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

The impact of equol-producing status in modifying the effect of soya isoflavones on risk factors for CHD: a systematic review of randomised controlled trials

Abstract: Recent studies suggest that the ability to produce equol, a metabolite of the soya isoflavone daidzein, is beneficial to coronary health. Equol, generated by bacterial action on isoflavones in the human gut, is biologically more potent than dietary sources of isoflavones. Not all humans are equol producers. We investigated whether equol-producing status is favourably associated with risk factors for CHD following an intervention by dietary soya isoflavones. We systematically reviewed randomised controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…For example, daidzein and genistein were reported to have a synergistic effect on inhibiting cell proliferation and inducing apoptosis of prostate cancer cells [ 14 ]. In addition, these compounds and equol were also proposed to be antiestrogenic, antioxidative, and anticarcinogenic and may protect against chronic diseases such as hormone-dependent cancer, cardiovascular diseases, and osteoporosis [ 15 19 ]. However, it is worth noting that a few studies considering estrogenic effects of dietary soy phytoestrogens have demonstrated that the isoflavones promote growth of ER-positive breast cancer cells under both in vitro as well as in vivo conditions [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, daidzein and genistein were reported to have a synergistic effect on inhibiting cell proliferation and inducing apoptosis of prostate cancer cells [ 14 ]. In addition, these compounds and equol were also proposed to be antiestrogenic, antioxidative, and anticarcinogenic and may protect against chronic diseases such as hormone-dependent cancer, cardiovascular diseases, and osteoporosis [ 15 19 ]. However, it is worth noting that a few studies considering estrogenic effects of dietary soy phytoestrogens have demonstrated that the isoflavones promote growth of ER-positive breast cancer cells under both in vitro as well as in vivo conditions [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…; Birru et al . ; Frankenfeld ). The definition of the equol producer phenotype is currently based on urinary or serum equol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, a number of human randomized controlled trials found beneficial effects of soy intake in equol-producing subjects but not in nonproducers. Those effects include improvement of risk factors for breast cancer, prostate cancer, cardiovascular disease and alleviation of osteoporosis (Shor et al 2012;Birru et al 2016;Frankenfeld 2017). The definition of the equol producer phenotype is currently based on urinary or serum equol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The soya isoflavone daidzein has strong anti‐inflammatory activity and affects various mechanism pathways including the NF‐κB, p38MAPK, and TGF‐ β1 pathways . Recent clinical studies have suggested that the ability to produce equol, a metabolite of the soya isoflavone daidzein, is beneficial against coronary heart disease . Puerarin and daidzein are the major bioactive isoflavonoids isolated from Puerariae radix .…”
mentioning
confidence: 99%
“…27 Recent clinical studies have suggested that the ability to produce equol, a metabolite of the soya isoflavone daidzein, is beneficial against coronary heart disease. 28,29 Puerarin and daidzein are the major bioactive isoflavonoids isolated from Puerariae radix. DW1029M protects against diabetic complications such as DN and diabetic retinopathy through the inhibition of advanced glycosylation end product formation rat lens aldose reductase activity, and TGF-β1 signaling.…”
mentioning
confidence: 99%